Differences in anxiety and some behaviors caused by covid between Croatian and foreign wrestlers - Rozic, F.; Baic, M.; Pekas, D. (International Journal of Wrestling Science, 2022)
INTRODUCTION: In 2020, 2021 and part of 2022, COVID 19 caused changes in the lives of a large number of people. The media has greatly influenced the behavior and anxiety of people in the world. This problem has especially resonated in sports, where training and a large number of competitions are prohibited. The aforementioned was expressed in wrestling. The aim of this work is to determine the differences in anxiety and behaviors caused by the COVID 19 pandemic between Croatian national wrestling representatives and national wrestling representatives from foreign national teams (Arm, Aus, CZ, Fin, Lit, Hun, Mol, Pol, Ned, Por, SAD, Esp, Srb, Swe, Sui, Ukr).